Comparative analysis of the Rotarix™ vaccine strain and G1P[8] rotaviruses detected before and after vaccine introduction in Belgium - Zeller, Mark (PeerJ, 2017)
G1P[8] rotaviruses are responsible for the majority of human rotavirus infections worldwide. The effect of universal mass vaccination with rotavirus vaccines on circulating G1P[8] rotaviruses is still poorly understood. Therefore we analyzed the complete genomes of the Rotarix™ vaccine strain, and 70 G1P[8] rotaviruses, detected between 1999 and 2010 in Belgium (36 before and 34 after vaccine introduction) to investigate the impact of rotavirus vaccine introduction on circulating G1P[8] strains. All rotaviruses possessed a complete Wa-like genotype constellation, but frequent intra-genogroup reassortments were observed as well as multiple different cluster constellations circulating in a single season. In addition, identical cluster constellations were found to circulate persistently over multiple seasons. The Rotarix™ vaccine strain possessed a unique cluster constellation that was not present in currently circulating G1P[8] strains. At the nucleotide level, the VP6, VP2 and NSP2 gene segments of Rotarix™ were relatively distantly related to any Belgian G1P[8] strain, but other gene segments of Rotarix™ were found in clusters also containing circulating Belgian strains. At the amino acid level, the genetic distance between Rotarix™ and circulating Belgian strains was considerably lower, except for NSP1. When we compared the Belgian G1P[8] strains collected before and after vaccine introduction a reduction in the proportion of strains that were found in the same cluster as the Rotarix™ vaccine strain was observed for most gene segments. The reduction in the proportion of strains belonging to the same cluster may be the result of the vaccine introduction, although natural fluctuations cannot be ruled out.